Adicción tecnológica y su incidencia en el estado de ansiedad de un adolescente de 16 años de edad, del cantón Babahoyo - Vera Maldonado, Luis Nol (2021)
Through the present case study, which arises from the concern that exists in a case of anxiety presented in an adolescent from the city of Babahoyo, induced by addictive behaviors to new technologies, especially mobile phones and the Internet, when carry out a series of activities online that occupy most of your time, and that in turn significantly affect social, family, and school areas, without leaving aside the physical and mental effects, emphasizing mainly on this last aspect, triggering a series of harmful behaviors such as; affectations in personal relationships; the inability to initiate and maintain a conversation with real staff and in real time, physical and mental exhaustion, poor school performance, and mainly its influence on the generalized anxiety state detected in the adolescent; the same one that is characterized by excessive worries of all kinds, feelings of overwhelm and tension, difficulty concentrating and sleeping, among other characteristic features. For the respective data collection in information, some diagnostic assessment techniques were implemented, such as the application of the Beck Anxiety Inventory (BAI) and the Kendall and Wilcox Self-control scale, in addition to the use of a Multicage web screening questionnaire. -ICT, to measure technological addiction in cybernetic users, the aforementioned evaluative tools were essential to identify the set of signs and symptoms that occurred in the patient due to their addiction to new technologies, in order to determine the influence, it has this condition on the state of anxiety presented.